Analisis Faktor Pendorong dan Penarik pada Pengembangan Minat Usaha: Kajian Sistematis dalam Model Jodyanne Kirkwood - Aini Ashary; Muh. Husriadi; La Ode Muhammad Juanda (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
Push and pull factors have long served as two explanatory poles in entrepreneurial motivation research. Jodyanne Kirkwood's (2009) model proposes an integrative approach that transcends this conventional dichotomy by demonstrating that both factors operate simultaneously within entrepreneurs. This systematic review aims to map how push and pull factors are operationalized in the literature, to identify the factor configurations most consistently associated with entrepreneurial interest development, and to evaluate the relevance of Kirkwood's model against recent empirical findings. Following the PRISMA protocol, 186 articles were identified from Google Scholar, Scopus (open access filter), and DOAJ; after staged screening, 15 articles met the inclusion criteria and were analyzed thematically. Findings indicate that pull factors, particularly the desire for independence, opportunity recognition, and achievement aspiration, predominate across research contexts, while push factors function more as enabling contexts than sole causal drivers. The push-pull interaction proves more nuanced than previously assumed; this review affirms the relevance of Kirkwood's model while identifying contextual dimensions that warrant expansion, especially in developing-country applications such as Indonesia.